Loyalty among online food delivery customers: Extended scale of e-service quality - Hernando, Hendrick; Gunawan, Wely Hadi (Universitas Kristen Maranatha, 2021)
Considering the contradictory finding regarding e-service quality influence toward customer loyalty in the context of online food delivery (OFD) service, we evaluate e-service quality measurement by adding an extended indicator. Our study aims to validate payment flexibility as an extended indicator and examine e-service quality influence on customer loyalty. Data were collected through an online questionnaire involving 100 OFD customers in West Java (Indonesia). The Partial Least Square (PLS-SEM) technique was used to analyze data from that answered questionnaire. Interestingly, our findings showed that payment flexibility is valid and reliable as an e-service quality indicator. Moreover, the influence of e-service quality on OFD customer loyalty is found to be statistically significant. Finally, this study provides new insight into the existing knowledge of e-service quality and generates valuable implications. OFD service providers are suggested to ensure order suitability in retaining their customer loyalty.